2022
DOI: 10.53046/ijotem.1175532
|View full text |Cite
|
Sign up to set email alerts
|

The Basıc Skılls in Socıal Studıes Textbooks

Abstract: Bu çalışmada 2018 yılında güncellenen Sosyal Bilgiler Öğretim Programında yer alan temel becerilerin 5, 6 ve 7’ nci sınıf sosyal bilgiler ders kitaplarında nasıl yer aldığı araştırılmıştır. Öğretim programında 27 adet temel beceri vurgulanmış ve bu beceriler tek tek açıklanmasa da her bir öğrenme alanında kazandırılması hedeflenen beceriler yer almıştır. Ancak bu becerilerin ders kitaplarına yansıyıp yansımadığı veya nasıl yansıdığı önemli bir problem durumu olarak görülmelidir. Nitekim temel becerilerin öğren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In line with the opinions, he received from the primary school teachers included in his study, the researcher stated that the basic concepts underlying the skills remained abstract for students, there was insufficient course time allocated for the implementation of the curriculum, and there were problems in terms of teaching materials and teacher competencies. Altay (2020) and Doğan and Oruç (2022) conducted research on the basic skills included in secondary school Social Studies textbooks. Altay (2020) concluded that skills in textbooks are not distributed evenly across grade levels and the frequency of use of skills in textbooks differs from each other.…”
Section: Skills Teaching and Social Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the opinions, he received from the primary school teachers included in his study, the researcher stated that the basic concepts underlying the skills remained abstract for students, there was insufficient course time allocated for the implementation of the curriculum, and there were problems in terms of teaching materials and teacher competencies. Altay (2020) and Doğan and Oruç (2022) conducted research on the basic skills included in secondary school Social Studies textbooks. Altay (2020) concluded that skills in textbooks are not distributed evenly across grade levels and the frequency of use of skills in textbooks differs from each other.…”
Section: Skills Teaching and Social Studiesmentioning
confidence: 99%
“…Altay (2020) concluded that skills in textbooks are not distributed evenly across grade levels and the frequency of use of skills in textbooks differs from each other. Doğan and Oruç (2022) also found that there are problems regarding the acquisition and subject context in which the skills will be used. The opinions that Mutluer (2013) received from Social Studies teachers regarding skill teaching revealed that both teacher competencies and students' performance in the course can be effective in acquiring skills.…”
Section: Skills Teaching and Social Studiesmentioning
confidence: 99%